Social influence in using ICT among fisherman in Malaysia - Mazuki, Raidah; Omar, Siti Zobidah; Bolong, Jusang; D' Silva, Jeffrey Lawrence; Abu Hassan, Musa; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2013)
One of the main factors that changes individuals’ behavior is social influence. Social influence is defined as a change in an individual’s thinking, feelings, attitudes, or behavior that results from interaction with other individuals or groups. Within the scope of ICT adoption among fishermen, social influence is expected to spread, and this study attempts to discover the social influence that impinges on fishermen’s use of ICT in their fishing routine. This is a quantitative study in which a total of 400 respondents have been selected based on multi-stage simple random sampling. SPSS is used to gain the required analyses, and descriptive analysis is also performed. The results reveal that social influence has less impact on fishermen’s use of ICT based on the low level of mean scores recorded for each of the eight statements studied.